Effective root planing for biologically acceptable root surfaces: an experimental study - Tsumanuma, Yuka; Khemwong, Thatawee; Izumi, Yuichi; Nozaki, Kosuke; Mikami, Ryo; Kano, Chihiro; Kobayashi, Hiroaki; Sudo, Takeaki (Journal of the Japanese Society of Periodontology, 2020)
Periodontal treatment is performed to achieve a biologically acceptable exposed root surface. Root planing removes the part of the root surface that contains inflammation-inducing substances. Previous studies reported that lipopolysaccharide (LPS) existed on superficial exposed root surfaces and deep root planing was not necessary for periodontal treatment. However, recently, it was reported that not only LPS but also various pathogen-associated molecular pattern molecules (PAMPs) and damage-associated molecular pattern molecules (DAMPs) cause biological immune responses. Advanced therapies, such as periodontal tissue regeneration, use periodontal ligament stem cells (PDL-MSCs), but the influence of substances on the PDL-MSCs on the root surface is unclear.In this study, we analyzed the permeability of the inflammation-inducing substance on the root surface to determine a suitable root surface for optimal periodontal regeneration.Extracted teeth were planed, and the shaving extracts from root surfaces were used to measure the bacterial genome. The IL-1β expression in THP-1 cells stimulated by the shavings was measured and the production pathway of IL-1β was investigated using inhibitors. PDL-MSCs were used to examine cell attachment and proliferation on the planed root surface.By laser microscope, the root planed depth of the periodontitis-affected exposed root surface was 32.2±3.86 μm after the first stroke, 51.9±9.31 μm after the second, 85.4±10.2 μm after the third, and 96.2±4.64 μm after the fourth stroke. Bacterial genome and IL-1β mRNA expression were detected from all shaving extracts up to 8 strokes. The 3-stroke planing showed a significantly high number of PDL-MSCs on the planed root surface. PAMPs and DAMPs in the shaving extracts were involved in the IL-1β production pathway.These results indicated that bacterial penetration was observed up to at least the eighth stroke and 3-stroke root planing was necessary for the adherence of the PDL-MSCs.Our research highlights the need for further studies by setting a standard for the ideal preparation of a root surface to receive periodontal stem cells for regenerative procedures.